Nivel de ansiedad y depresión en escolares de 4to, 5to y 6to de primaria durante el aislamiento social por COVID-19 - Campos Pérez, Juan Grabiel (2023)
The World Health Organization (WHO) declared the outbreak of the SARS COV-2 virus (Covid-19) as a pandemic on March 11, 2020. The world was informed of its high degree of contagion, alerts were issued regarding the consequences and impact on the public health, social and economic sectors in all countries. Worldwide, quarantine was one of the preventive measures to stop the spread of Covid-19, including the closure of schools, which meant great changes in lifestyles for students; such as work, education, meetings and recreational activities, implementing virtuality as a new lifestyle. Objective: ▪ To establish the relationship between the level of anxiety and depression in fourth, fifth and sixth grade schoolchildren during social isolation due to covid-19 of the Educational Institution "San Francisco de Asís - N°80038" of the district of La Hope in the 2020 – 2021 school year. Method: Observational, prospective, cross-sectional and analytical study. 151 students from 4th to 6th grade of primary education were surveyed. Results and conclusions: The results were presented in simple and double entry statistical tables; After the analysis, it was concluded that: level of anxiety (absence of anxiety 45.7%, mild 36.4%, moderate 14.6%, high 3.3%. However, in 5th grade, 47% presented mild anxiety), level of depression (mild 50.3 %, moderate 29.8%, absence of depression 18.5%, high 1.3%). There is no significant relationship between the level of anxiety and the level of depression (p > 0.05).